Correlates of perceived risk of HIV infection among persons who inject drugs in Tijuana, Baja California, Mexico - Richard F Armenta (Salud Pública de México, 2015)
Objective. We identified correlates of perceived risk of HIV infection among persons who inject drugs (PWID) in Tijuana. Materials and methods. PWID ≥ 18 years of age who injected drugs in the past month were recruited between 2006-2007 and completed risk assessment interviews and serologic testing for HIV, syphilis, and tuberculosis. Logistic regression was used to determine factors associated with high-perceived risk of HIV infection. Results . Among 974 PWID, HIV prevalence was 4.4%; 45.0% of participants perceived themselves to be more likely to become HIV infected relative to other PWID in Tijuana. Participants who reported high-perceived risk of HIV infection participated in high-risk behaviors such as injecting with used syringes, transactional sex, and were less likely to have had an HIV test. Conclusions. Recognition of HIV infection risk was associated with high risk behaviors and markers of vulnerability. Findings support efforts to encourage HIV testing and access to health care for this vulnerable population.